MICROPARTICLE SEPARATION IN A LINEAR PAUL TRAP - Syrovatka, Roman; Filinov, Vladimir; Vasilyak, Leonid; Pecherkin, Vladimir; Deputatova, Lidiya; Vladimirov, Vladimir (Journal of Applied Engineering Science, 2021)
We investigated the charged micron-sized particle separation by the alternating electric field in a linear quadrupole electrodynamic trap in open air under standard atmospheric temperature and pressure conditions (STP). In experiments we varied the amplitude of the alternating voltage supplying the electrodynamic trap and used a mixture of charged glassy carbon and alumina particles. The carried out numerical simulations and experimental results showed the mutual influence of the amplitude and frequency of the supplied to the trap electrode voltage on the separation of the different sizes particles. The typical particle charges in simulations were approximately equal to experimentally measured values obtained in a corona discharge.
Keywords: separation; microparticles; Paul trap; charged particles